Importance of the academic blog in learning the area of communication in the educational institution Villa Heart of Jesus – Tusi - Pasco - 2022 - Tapia-Poma, Angela A. (2023)
The current work assumed as objective: To determine the importance of the academic blog in the learning of the Communication Area in the Educational Institution Villa Corazón de Jesús-Tusi-Pasco-2022. It was proposed as dimensions to communicate orally in their mother tongue, read various types of texts in their mother tongue and write various types of texts in their mother tongue. The final research report used the APPLIED type methodology, because the established problem requires a practical solution and with an experimental design applying a pre-test and post-test working with a single group, its instrument that will be used for data collection. In both variables. After reviewing the results obtained where it was sought to determine the importance of the academic blog in the learning of the Communication Area in the Villa Corazón de Jesús-Tusi-Pasco Educational Institution, from which significant results were obtained. In conclusion, it has significant importance on the dependent variable, because 99.2% demonstrate the significant importance of the academic blog strategy in learning the Communication Area, in primary level students, compared to 0.8% who found that there was no significant influence of one variable on another.Key words: academic, learning, oral, texts, communicate, read, write, blog.